Analisis Ketersediaan dan Kebutuhan Lahan Parkir Pada RS. Bhayangkara Makassar - Hendrawan Djoni; Robert Mangontan; Monika Datu Mirring Palinggi (Paulus Civil Engineering Journal, 2023)
Parking does not escape the area of the hospital area, so it is not complete if the hospital is not equipped with a parking lot. When the parking characteristics have been met, it will make it easier for employees and visitors to park their vehicles, both two-wheeled and four-wheeled vehicles. Analysis of parking characteristics, availability, and demand in hospitals. Bhayangkara Makassar is the aim of this research. This study uses direct field surveys as its methodology for obtaining vehicle data. From this data will be analyzed to obtain data on parking capacity, parking volume, parking accumulation, parking duration, parking index, availability and demand for parking space. The results revealed that there were parking spaces up to 54 and 84 vehicles per hour for motorbikes and cars, 620 cars and 1,025 vehicles, each maximum parking volume, the highest parking accumulation of 4,072 vehicles and 9,745 vehicles, the vehicle parking duration ranged from 1-2 hours for both, parking index of 109.20% and 102.43%, the availability of maximum parking is 466 vehicles/hour. According to the parking characteristics, it can be concluded that the current parking area is not sufficient to accommodate the number of parked vehicles.